Detection of Bacteriophage Particles Containing Antibiotic Resistance Genes in the Sputum of Cystic Fibrosis Patients - Brown-Jaque, Maryury; Rodriguez Oyarzun, Lirain; Cornejo-Sánchez, Thais; Martín-Gómez, Maria T.; Gartner, Silvia; de Gracia, Javier; Rovira, Sandra; Alvarez, Antonio; Jofre, Joan; González-López, Juan J.; Muniesa, Maite (Frontiers in Microbiology, 2018)
Cystic fibrosis (CF) is a chronic disease in which the bacterial colonization of the lung is linked to an excessive inflammatory response that leads to respiratory failure. The microbiology of CF is complex. Staphylococcus aureus is the first bacterium colonizing the lungs in a 30% of paediatric patients. Later, a 80 % of adult CF patients develop a chronic Pseudomonas aeruginosa infection, and other microorganisms can also be found. The use of antibiotics is essential to treat the disease, but antibiotic performance is compromised by resistance mechanisms. Bacteriophages have recently been reported to constitute one of the various mechanisms of transfer of antibiotic resistance genes (ARGs), and are the least explored in clinical settings. Here we evaluate their presence in CF patients. 71 sputum samples of CF patients were used to quantify eight ARG (blaTEM, blaCTX-M-1-group, blaCTX-M-9-group, blaOXA-48, blaVIM, mecA, qnrA and qnrS) in the bacteriophage DNA fraction. The phages found were also purified and observed using electron microscopy. 32.4 % of CF patients contain ARGs in phage DNA. β -lactamase genes, particularly blaVIM and blaTEM, were the most prevalent and abundant, whereas mecA, qnrA and qnrS were very rare. Siphoviridae phage particles capable of infecting P. aeruginosa and Klebsiella pneumoniae were detected in the CF sputum. Phage particles harbouring ARGs were abundant in the lungs of both CF patients and healthy people and could contribute to the colonization of multiresistant strains.